2019
DOI: 10.29298/rmcf.v1i1.649
|View full text |Cite
|
Sign up to set email alerts
|

Planificación De Sistemas De Áreas Verdes Y Parques Públicos

Abstract: RESUMENEl análisis de algunos sistemas de áreas verdes y parques públicos de Curitiba (Brasil), Ciudad de México (México), Madrid (España), Nueva York (Estados Unidos de América) y Santiago (Chile) evidencia problemas comunes como el déficit de superficie verde, la inseguridad y los riesgos de exclusión social. A lo anterior se añade la ausencia de valor monetario de los servicios que prestan dichos sistemas naturales como recreación y conservación. En conjunto, son factores importantes en la asignación de ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
0
7
0
7
Order By: Relevance
“…Toda vez que estos espacios proporcionan a las ciudades y a sus habitantes servicios ambientales como regulación del clima, control de la erosión, recreación, turismo, polinización, estética, hábitat para fauna silvestre, captura de carbono, conservación de la biodiversidad, entre otros (Mora-Olivo y Martínez, 2012;Gómez-Baggethun et al, 2013). Por ello resulta relevante el conocimiento de las mismas en lo referente a su estructura, composición y diversidad para fortalecer la planificación y la gestión de los ámbitos verdes urbanos para las presentes y futuras generaciones (Flores-Xolocotzi y González-Guillén, 2010).…”
Section: Introductionunclassified
“…Toda vez que estos espacios proporcionan a las ciudades y a sus habitantes servicios ambientales como regulación del clima, control de la erosión, recreación, turismo, polinización, estética, hábitat para fauna silvestre, captura de carbono, conservación de la biodiversidad, entre otros (Mora-Olivo y Martínez, 2012;Gómez-Baggethun et al, 2013). Por ello resulta relevante el conocimiento de las mismas en lo referente a su estructura, composición y diversidad para fortalecer la planificación y la gestión de los ámbitos verdes urbanos para las presentes y futuras generaciones (Flores-Xolocotzi y González-Guillén, 2010).…”
Section: Introductionunclassified
“…Representative samplings of Mexico City's urban forest have been conducted since the decade of the 1990s (Chacalo, Aldama, & Grabinsky, 1994;Meza, 1992), however, the majority of studies have been centered on green public spaces and vegetation cover in relation to distribution, ecological and socio-demographic characteristics, management and planning (Checa-Artasu, 2016;Flores Xolocotz & González-Guillén, 2012;Flores Xolocotzi, González-Guillén, & de los Santos-Posadas, 2010;Meza Aguilar, 2015;Robles, 2014). The urban forests of Mexico City has been studied with a wide variety of approaches and methodological tools but inventories of Mexico City's trees are scant relative to modern analysis technics using remote sensing tools and images collected via satellites.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of successful governance for UGI mentioned in the research found included environmental education (Ferrer et al, 2010;Barroso and Mesquita, 2014;Costa Cardoso et al, 2015;Benchimol et al, 2017;Pabello and Nasupcialy, 2019), recreational opportunities and tourism (Sanchotene, 1994;García and Guerrero, 2006;Guerrero and Culós, 2007;Flores-Xolocotzi and González-Guillén, 2010), investment (Flores-Xolocotzi, 2012;Babilonia et al, 2018), easing the transition of the urban-rural interface (Gurovich Weisman, 2003), and environmental benefits such as climate change adaptation and reduced flood risks (Granados-Olivas et al, 2016;Millington, 2018;Flores et al, 2019;Giner et al, 2019). Nail and Erazo (2018) made the case for state-initiated self-governance initiatives for post-conflict peace building, a link between UGI and social capital that was also made by Ferrer et al (2010), Costa Cardoso et al (2015), Sánchez (2019), and Visoni and Nagib (2019, p. 88).…”
Section: Benefits Of Successful Governancementioning
confidence: 98%
“…With reference to the relation between geographical spread to the temporal trends shown in Figure 4, the few publications on UGI management before 2003 were from, and centered on, Brazil. Although being the sole focus of almost 20% of the research, the first study on Mexico within the articles found was a comparative study of Brazil, Mexico, Chile, Spain, and the US in 2010 (Flores-Xolocotzi and González-Guillén, 2010). The first studies to focus on Mexico alone were not published until 2015, showing a recent rise in academic interest in UGI management in the country.…”
Section: Overview Of the Researchmentioning
confidence: 99%